KARAKTERISTIK MINYAK WIJEN (Sesamum indicum L.) SANGRAI SELAMA TAHAPAN PROSES PEMURNIAN - , ARBA SUSANTY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Roasting can produce sesame oils with a good flavor, high nutrition and antioxidant activity. Sesame seed roasting also extracted some impurities such as free fatty acid, peroxide, phosphatide and makes a dark color of oils. These impurities influence the oils quality. The refining steps have specific purposes to decrease these impurities. The objective of this research is to observe the changes of color, phosphor, peroxide value, free fatty acid, antioxidant activity, total phenolic compound and iodine value of roasted sesame oil during refining process: degumming, bleaching and deodorization. Sesame oil research was conducted with the preparation of sesame oil with roasted the sesame seed at temperature 220oC for 30 minutes and pressing. Roasted sesame oil then degummed by comparing the three methods degumming with water, acid and water acid and alkali. A best result from degumming method is then followed by bleaching and deodorization. Analysis of data obtained in this study, processed using program statgraphic xv plus for windows. Degumming process with water acid and alkali can decrease phosphorus 96%, free fatty acid 76% and peroxide value 57%. This method also decrease antioxidant activity 19% and total phenolic compound 66%. This roasted sesame oil have red color 3,5 and yellow 5,6. Bleaching process which using kaolin at 85oC for 25 minutes has no significant effect on roasted seame oil color. Deodorization process at 220oC, 40 mmHg with steam striping for 60 minutes can decrease free fatty acid 80%. This deodorized sesame oil have antioxidant activity 68,54%.